2018
DOI: 10.1002/ldr.3167
|View full text |Cite
|
Sign up to set email alerts
|

Continuous‐cropping tobacco caused variance of chemical properties and structure of bacterial network in soils

Abstract: Continuous cropping of the same crop leads to land degradation. This is also called the continuous-cropping obstacle. Here, we investigated how long-term continuous cropping of tobacco influences soil biochemical properties and bacterial networks in the mountain lands of China. Two different fields were sampled: one with 25 years of continuous cropping tobacco and one with noncontinuous cropping tobacco. Soil chemical and biological properties were measured including available phosphorus and potassium, soil or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 81 publications
(109 reference statements)
5
78
1
Order By: Relevance
“…Bacteria as well as plants secrete urease 49 . Continuous cropping causes a decline in the urease activity, and significant correlations between urease activity and bacterial networks have been previously found 50,51 . We found that TN was significantly correlated with microbial communities in all samples (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Bacteria as well as plants secrete urease 49 . Continuous cropping causes a decline in the urease activity, and significant correlations between urease activity and bacterial networks have been previously found 50,51 . We found that TN was significantly correlated with microbial communities in all samples (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…The topological roles of nodes in the BWS network are different from those in the HS network. The topological roles of nodes were defined by the within-module connectivity (Z i ) and among-module connectivity (P i ) (23,25,(29)(30)(31)(32) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Threshold values of Z i and P i for categorizing nodes are 2.5 and 0.62, respectively. According to the threshold values of Z i and P i proposed by previous research (23,25,(29)(30)(31)(32), the nodes were divided into four categories. (i) Peripheral nodes (named specialists) had low Z i (Ͻ2.5) and low P i (Ͻ0.62) values.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with NPTP (17 modules) and CTP soils (9 modules), OTP network had a more complex structure and a higher number of modules (22 modules) with topological characteristics ( Figure 5). Since highly connected microbial communities within a single module may have unique ecological functions [60], the structure of soil microbial network in organic tea gardens has more diverse ecological function groups, which is of great significance for improving the versatility of soil ecosystem [61]. On the contrary, the common tea garden soil network has the minimum number of topological modules (9 modules), which may lead to the hindrance of the exchange of information, energy and nutrients between microbial communities [60].…”
Section: Discussionmentioning
confidence: 99%